Preface - Ziemiański, Leon; Waszczyszyn, Zenon (Computer Assisted Methods in Engineering and Science, 2011)
This Special Issue contains papers related to the Special Sessions on Artificial Neural Networks (ANNs) in Civil Engineering, organized at the 57th Annual Conference on Scientific Problems of Civil Engineering (CE). The conference called for short Krynica 2011 was organized by the Rzeszów University of Technology under the auspices of the Committee of Civil Engineering of the Polish Academy of Sciences and the Polish Association of Civil Engineers and Technicians. The Special Issue II contains eight papers. The first paper of the state-of-the-art character deals with various applications of ANNs in geomechanics, and especially, in soil mechanics. Three supplementary survey papers are devoted to the granular soils identification problems. A hybrid system of high degree of components interaction is discussed as a new approach for identification of an equivalent neural material model. The identification of soil compact characteristics and parametric identification of soil in a deep excavation are then analyzed. Four papers concern mechanics of concrete, R/C column buckling and repair of concrete industrial floors. The application of various non-standard ANN models and algorithms (Bayesian methods, Gaussian Processes, Kalman Filtering and Fuzzy Weight AN) are worth mentioning.